Effect of 17α-Methyltestosterone Hormone Manipulation in Various Water Temperatures on Sex Ratio of Guppy (Poecilia reticulata Peters) - H. Arfah; A.K. Kadriah; O. Carman (Jurnal Akuakultur Indonesia)
This study was conducted to determine percentage of male progeny of guppy (Poecila reticulata Peters) broodstock immersed in water containing various dose of 17α-Methyltestosterone (MT) and different temperature.  Immersion of broodstock was carried out at 10th day after spawning.  Dosage of MT used was 0, 0.5 and 1 mg per liter of water, while the water temperature was 27, 30 and 33oC, for 24 hours immersion.  The result of study showed that the combination of hormone treatment 1mg/L and temperature 27oC produced higher percentage of male progeny (92.7%).  Increasing water temperature in combination with dose of hormone treatment can reduce percentage of male progeny.